Android Based Thesis Mentoring System Using Google Firebase - Mychael Maoeretz Engel (Bina Nusantara University, 2018)
This research aimed to build a platform to carry out the thesis mentoring process which was periodic, real-time, systemized, and well-integrated in Ciputra University in Surabaya. The researcher used Google Firebase technology provided by Google and built it on an Android-based platform. The method used was the Systems Development Life Cycle (SDLC) model. It was divided into six stages of the process: requirement analysis, system design, implementation, system testing, system deployment, and system maintenance. Data collection methods used were observation and interviews conducted to the final project coordinator in the study program. The results show that system has six main features including progress overview of thesis, chat room, guidance schedule, guidance book, important date, and announcement. Moreover, the thesis mentoring system is easy to use and consists of easyto-understand menus. After going through the process of analysis, this system is very helpful in scheduling guidance, monitoring the progress of student thesis work, and managing announcement and important date.